Prilaku Perjalanan Penduduk Pinggiran Kota dan Asosiasinya dengan Sebaran Fasilitas Perkotaan - Heru Purboyo Hidayat Putro; Ridwan Sutriadi; Santi Maulani (Journal of Regional and City Planning, 2008)
The economic development relying on cities tends to attract peoplefrom rural area to migrate to big cities. This urbanization whichhappened rapidly in urban fringe area, especially get realised bythe new housing development. Eventhough people lived becamemore far from the urban centre, urban service is still concentratedin old urban part. This paper presents the research 's resultsconcerning daily people travel related with their main activity. Themethod is primary survey, using questionnaires which weredistributed to households who live in the fringe area. They wereasked about their routinity, which was related with working,studying, and shopping. Case study was chosen for urban fringe incities of Bandung and Semarang. The ï¬ndings show that Bandungand it 's urban fringe area were dense and compact related to thefacilities distribution, whereas Semarang was less compact and lessdense. The ï¬ndings also show that people who lives in compactfringe area were travelling shorter than people who lived in lesscompact fringe area. Related with public transport, level of serviceinï¬‚uences people to change the transport mode, and it was notcaused by the length of trip.